Respiratory sounds in healthy people: a systematic review - Oliveira, Ana (2019)
There is a lack of systematised information on respiratory sounds of healthy people. This impairs health professionals from differentiating respiratory sounds of healthy people from people with respiratory diseases, which may affect patients' diagnosis and treatment. Therefore, this systematic review aimed to characterise respiratory sounds of healthy people.